Regulation of hepatic glucose production and AMPK by AICAR but not by metformin depends on drug uptake through the equilibrative nucleoside transporter 1 (ENT1). Issue 12 (2nd August 2018) - Logie, Lisa; Lees, Zoe; Allwood, J. William; McDougall, Gordon; Beall, Craig; Rena, Graham
Abstract : Aim: Recently we have observed differences in the ability of metformin and AICAR to repress glucose production from hepatocytes using 8CPT‐cAMP. Previous results indicate that, in addition to activating protein kinase A, 8CPT‐modified cAMP analogues suppress the nitrobenzylthioinosine (NBMPR)‐sensitive equilibrative nucleoside transporter ENT1. We aimed to exploit 8CPT‐cAMP, 8CPT‐2‐Methyl‐O‐cAMP and NBMPR, which is highly selective for a high‐affinity binding‐site on ENT1, to investigate the role of ENT1 in the liver‐specific glucose‐lowering properties of AICAR and metformin. Methods: Primary mouse hepatocytes were incubated with AICAR and metformin in combination with cAMP analogues, glucagon, forskolin and NBMPR. Hepatocyte glucose production (HGP) and AMPK signalling were measured, and a uridine uptake assay with supporting LC‐MS was used to investigate nucleoside depletion from medium by cells. Results: AICAR and metformin increased AMPK pathway phosphorylation and decreased HGP induced by dibutyryl cAMP and glucagon. HGP was also induced by 8CPT‐cAMP, 8CPT‐2‐Methyl‐O‐cAMP and NBMPR; however, in each case this was resistant to suppression by AICAR but not by metformin. Cross‐validation of tracer and mass spectrometry studies indicates that 8CPT‐cAMP, 8CPT‐2‐Methyl‐O‐cAMP and NBMPR inhibited the effects of AICAR, at least in part, by impeding its uptake into hepatocytes. Conclusions: We report for the first time that suppression of ENT1 induces HGP. ENT1 inhibition also impedes uptake and the effects of AICAR, but not metformin, on HGP. Further investigation of nucleoside transport may illuminate a better understanding of how metformin and AICAR each regulate HGP.